Choose Entrepreneurship Amidst Difficult Job Opportunities: Dilemmas for High School/Vocational High School Graduates in Sidenreng Rappang Regency in Determining the Type of Business - Salida, Amrizal; Haeril, Haeril; Yunus, Idris; Kadir, Abdul (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
The purpose of this study is to explore the dilemmas faced by high school and vocational school graduates in Sidenreng Rappang Regency when deciding what type of business to start, given the limited availability of job opportunities. The study uses an exploratory and interactionist qualitative approach, with data collected through in-depth interviews, observation, and documentation. The data were then analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing/verification, supported by data triangulation to ensure the validity of the findings. To facilitate the data analysis process, NVivo software was also used. The results reveal a complex dilemma in determining the type of business to pursue. This issue is influenced not only by limited financial capital, but also by psychological factors, practical skills, market access, and the lack of external guidance. These barriers are multidimensional, involving both individual and structural aspects, where fear of debt, low self-confidence, and limited experience further intensify the challenges. Despite these constraints, there are potential business opportunities that can be accessed with minimal capital, such as online trading, service-based skills, culinary ventures, agribusiness, and non-formal education. Graduates tend to adopt adaptive strategies such as self-directed learning, starting small businesses, relying on family support, and using digital technology. However, these strategies alone are not sufficient to ensure business sustainability without external support. In conclusion, entrepreneurial readiness among graduates is shaped by a combination of financial capital, social capital, self-confidence, and structural support. Therefore, entrepreneurial success largely depends on the synergy between individual capacity and a sustainable supporting ecosystem.